Overburdened Chinese Compulsory Education Teachers - Tang, Yun (Science Insights Education Frontiers, 2023)
The universalization of “nine-year compulsory education” in China has significantly augmented the teaching force at this level. Compulsory education teachers are the most crucial human resource for the development of this system. However, they have been under disproportionately heavy work burdens, which are detrimental to their mental and physical health and compromise the quality of education. This article focuses on presenting the signs of overburden among compulsory education teachers and pinpointing its causes, with the purpose of contributing to alleviating the job strain of this group and developing a sustainable compulsory education.